English as a Crucial Tool in International Business Communication - Lisowska, Justyna (Język angielski jako kluczowe narzędzie komunikacji w biznesie międzynarodowym, 2022)
With globalisation shifting world’s economies towards a common market, the need for a shared mean of communication emerged. The aim of this article is to recognise the importance of English as a contemporary communication tool in international business and identify underlying opportunities and weaknesses arising from one’s proficiency. Simultaneous considerations cover the roots of assigning the lingua franca role to English and illustrate its varieties among speakers. The research methods used to evaluate the issue are descriptive, comparative, and include the analysis of the literature on the subject. The examined literature is based on quantitative research methods that are used to identify economic benefits of English usage. Moreover, chosen qualitative methods are used to discover socio-cultural settings and individuals within them. The results encapsulate economic, cultural and technological potential of English by presenting key areas in which it can be applied strategically to achieve long-lasting benefits.
[w:] Ekonomia i międzynarodowe stosunki gospodarcze / pod red. Aleksandry Kuźmińskiej-Haberli. - Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2022, s. 89-105
Keywords: international communication; English language; business communication; linguistic diversity; komunikacja międzynarodowa; język angielski; komunikacja biznesowa; różnorodność językowa